The Art of Singing Culture: Modern World Picture - D.K., Kudaibergen; A.K., Mussakhjayeva; T.Zh., Yeginbayeva (Journal of Posthumanism, 2025)
The study of the issue of the aesthetic specificity of vocal and performing arts made it possible to discover a very contradictory situation in scientific works. On the one hand, the history of vocal music has been studied in many ways, there are fundamental works on the problems of the connection between music and words (V. Vasina-Grossman, O. Sokolov), a methodology for analyzing melody, harmony, dramaturgy and composition of opera works has been deeply developed (L. Mazel, E Ruchevskaya, V. Kholopova), a theory of genres of vocal music was created (O. Sokolov), studies of the style of vocal music of individual composers and schools are widespread. On the other hand, it was not possible to find works specifically devoted to the vocal and performing arts as an aesthetic phenomenon. That is, there is a situation where the question “how is it done?” ahead of the question "what is it?".Starting with the treatises of Italian theorists of singing, in the scientific and methodological literature there is a significant part of the works, the title of which contains the words "art of singing". In vocal literature, singing is traditionally defined as "the art of correct voice formation", "the art of correct breathing", "a complex psychophysiological process ”, “a system for the correct use of resonators”, etc. Accordingly, researchers and authors of scientific works on vocal performing arts focus their attention on the analysis of various methods and techniques for teaching singing, the number of which has been accumulated since the time of the old Italian masters of the XYII century and which arise again and again.The need for work on the development and improvement of the singing voice and the right direction of the search for most specialists do not raise any doubts. And yet we will attempt a broader formulation of the question: about the aesthetic features of vocal performance, which distinguishes it from other types of art, about the performer as an artist, about the special power of his influence on personality and self-consciousness, and his ability to influence mass consciousness.The main means of artistic expression in vocal creativity, its aesthetic dominant is vocalization, which is primary in relation to the singer’s recitation. The human voice is music and poetry, where the sung word is the main part of the vocal text.The most important factor that largely determines the aesthetics of vocal art in its historical perspective is the problem of interaction and mutual influence between opera reforms and vocal art. Here it is necessary to stop briefly and outline the features of singing phonation that have arisen and exist outside the framework of the art of opera.Primitive music was composed of rhythm and intoned speech. Ritual- suggestive functions, rhythmization of joint labor activity, generalization of speech intonations in folk melodies - all this was created and polished over many millennia. But the birth of artistic singing, although it took place in ancient times, but this process is inextricably linked with the development of civilization, and, as a result, with the morphology of culture and social processes in society. The first musical instrument was the voice, and music, born as a reinforcement of the functions of sound communication, is associated with human speech. The art of the kifareds in ancient Greece, the pathetic genre of Greek tragedy, demanded from the performer the expressiveness of precisely the word “sung” by the actor. The genre of opera is born from the appeal of Renaissance musicians to the aesthetics of the ancient Greek theater. Throughout its history, the opera genre has repeatedly turned to the "word". In this case, the role of poetry, its rhythmic basis, prosody and phonetics of the language were to determine the aesthetics of singing.Another property is mimesis. Its influence on the vocal melody is different from the role of the word. Onomatopoeia and emotion play an important role in vocal performance, and singing as a psychophysiological process is closely related to the emotional nature of a person.The level of the singer’s emotional development, his emotional "range" and mobility, his ability for a vivid sensual experience is an integral part of vocal art.